The mechanical properties of tibiofemoral and patellofemoral articular cartilage in compression depend on anatomical regions - Heng Li; Jinming Li; Shengbo Yu; Chengwei Wu; Wei Zhang (Scientific Reports, 2021)
Abstract Articular cartilage in knee joint can be anatomically divided into different regions: medial and lateral condyles of femur; patellar groove of femur; medial and lateral plateaus of tibia covered or uncovered by meniscus. The stress–strain curves of cartilage in uniaxially unconfined compression demonstrate strain rate dependency and exhibit distinct topographical variation among these seven regions. The femoral cartilage is stiffer than the tibial cartilage, and the cartilage in femoral groove is stiffest in the knee joint. Compared with the uncovered area, the area covered with meniscus shows the stiffer properties. To investigate the origin of differences in macroscopic mechanical properties, histological analysis of cartilage in seven regions are conducted. The differences are discussed in terms of the cartilage structure, composition content and distribution. Furthermore, the commonly used constitutive models for biological tissues, namely Fung, Ogden and Gent models, are employed to fit the experimental data, and Fung and Ogden models are found to be qualified in representing the stiffening effect of strain rate.